Teori Kritis Habermas dan Relevansinya dengan Pendidikan - Fahri Hidayat (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2017)
This paper examines the critical theory developed by Jurgen Habermas, a philosopher of the second-generation Frankfurt school of thought. Critical views of Habermas in social science that many social scientists studied can be implemented into the world of education and formulated into a model of critical education. Habermas's critical theory and theory of communicative action for educational sociology are used as models of how social theory can influence in shaping thought and action in education. Habermas's critical theory contributes in enlightenment to an education that is more humanizing to human beings, rather than seeing humans as empty papers that do not exist.